Evaluation in projects combating educational poverty: challenges and strategies - Ghibellini, Valentina (Community Notebook. People, Education and Welfare in the Society 5.0, 2025)
Reporting the results of publicly funded projects is crucial and requires clearly defined evaluation indicators. This approach is especially important in calls aimed at addressing complex and dynamic social phenomena. Based on an analysis of impact evaluation experiences from projects addressing Educational Poverty, the paper explores the challenges faced in evaluation research and offers reflections and potential recommendations for enhancing its effectiveness.